Preliminary psychometrics of the Existential Distress Scale in patients with advanced cancer. (24th October 2016) - Lo, C.; Panday, T.; Zeppieri, J.; Rydall, A.; Murphy‐Kane, P.; Zimmermann, C.; Rodin, G.
Abstract : Existential distress is of clinical concern in patients with terminal illness. Although existential distress has been used to describe a broad spectrum of psychological disturbances, its narrower definition may be confined to distress that arises when the meaning and value of one's life is unclear, and is comorbid with feelings of loneliness and low self‐worth. To promote further study, we developed and pilot‐tested a 10‐item Existential Distress Scale (EDS). Twenty‐one patients with advanced cancer were recruited from a palliative care unit. Measures of existential distress, death anxiety, depression, performance status and physical symptom burden were collected. The EDS showed promising psychometric properties, including significant associations with death anxiety and depression. Thirty‐eight per cent of the sample reported great or unbearable distress on at least one existential concern. The EDS may be administered to measure existential distress in patients with advanced cancer and clinicians may find the instrument useful to initiate a structured discussion about this symptom.